Influence of Various Irrigation Protocols on Resistance to Vertical Root Fracture in Root Canal Treated Teeth - Ezgi Doganay Yildiz; Mehmet Fidan; Buket Dincer (Mashhad University of Medical Sciences, 2021)
Introduction: This study compared influence of various irrigation protocols on vertical root fracture resistance of root canal treated teeth. Methods: Forty-eight extracted mandibular premolars were included in the study. The root canals of teeth were instrumented and specimens were allocated into 4 (n = 12) groups according to the irrigation solutions: Group 1: 5% EDTA, 2.5% NaOCl and DW; Group 2: 5% EDTA, 2.5% NaOCl, DW and 2% CHX; Group 3: 5% EDTA, 2.5% NaOCl and 5% Na2S2O3; Group 4: 5% EDTA, 2.5% NaOCl, 5% Na2S2O3 and 2% CHX. Root canals were filled and a load in a vertical direction was applied a week later to specimens. The data were analysed using two-way ANOVA test (P < 0.05). Results: Interaction between using DW or Na2S2O3 and using or not using CHX had a significant effect on fracture resistance to vertical forces (P < 0.001). Irrigation with Na2S2O3 improves fracture resistance to vertical forces when compared to irrigation with DW (P < 0.001). Irrigation with CHX did not affect fracture resistance to vertical forces (P = 0.759). Conclusion: The irrigation solutions statistically affect resistance of root canal treated teeth to vertical fracture forces.